2023
DOI: 10.1002/jmv.29106
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, epidemiological, and genomic characteristics of a seasonal influenza A virus outbreak in Beijing: A descriptive study

Wentao Zhu,
Li Gu

Abstract: China experienced a severe influenza season that began at the end of February 2023. The aim of this post hoc analysis was to investigate the clinical, epidemiological, and genomic features of this outbreak in Beijing. The number of cases increased rapidly from the end of February and reached its peak in March, with 7262 confirmed cases included in this study. The median age was 33 years, and 50.3% of them were male. The average daily positive rate reached 69% during the peak period. The instantaneous reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…After the relaxation of NPIs, studies 13–15 had reported that in mainland China, influenza activity recovered in 2021 compared with that in 2020 and intensified during the traditional influenza winter season. When China ended its “Zero‐COVID” policy on December 7, 2022, a sharp increase in influenza A activity in February 2023 combined with the spreading of Omicron posed huge a threat to the public healthcare system 11,12 . The present study reported a retrospective observation on the cocirculation of multiple respiratory viruses in Beijing in 2023.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…After the relaxation of NPIs, studies 13–15 had reported that in mainland China, influenza activity recovered in 2021 compared with that in 2020 and intensified during the traditional influenza winter season. When China ended its “Zero‐COVID” policy on December 7, 2022, a sharp increase in influenza A activity in February 2023 combined with the spreading of Omicron posed huge a threat to the public healthcare system 11,12 . The present study reported a retrospective observation on the cocirculation of multiple respiratory viruses in Beijing in 2023.…”
Section: Discussionmentioning
confidence: 83%
“…When China ended its "Zero-COVID" policy on December 7, 2022, a sharp increase in influenza A activity in February 2023 combined with the spreading of Omicron posed huge a threat to the public healthcare system. 11,12 The present study reported a retrospective observation on the cocirculation of multiple respiratory viruses in Beijing in 2023.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The PANGO lineages of all genomes were determined according to the pangolin nomenclature. An in-house script was used to parse genomes with "N" and low coverage in order to identify the single nucleotide polymorphisms (SNPs) (21). The mutations in each genome were identified using Wuhan-Hu-1 as the reference.…”
Section: Variant Calling and Phylogenetic Analysismentioning
confidence: 99%
“…However, in the past decade, many regions worldwide have reported influenza outbreaks, such as Thailand 13 , Italy 14 , Taiwan 15 , and America 16 . Previous studies 17 20 on influenza largely focused on epidemiological characteristics and the analysis of influencing factors. In addition, Morabia 21 found that variation in social and healthcare-based determinants exacerbates influenza epidemics, and low socioeconomic status (SES) individuals are prone to bear the burden of infection.…”
Section: Introductionmentioning
confidence: 99%